2013
DOI: 10.1007/s00167-012-2329-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells for the treatment of cartilage lesions: from preclinical findings to clinical application in orthopaedics

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
174
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(177 citation statements)
references
References 84 publications
2
174
0
1
Order By: Relevance
“…1); five case studies (17,(22)(23)(24)(25)(26) were excluded and nine studies (24,(27)(28)(29)(30)(31)(32)(33)(34) were removed due to difficulties in extracting the outcome measurements. Four systematic reviews (35)(36)(37)(38) were also excluded. An assessment of the remaining 18 studies revealed that 10 used a single-arm prospective design (18)(19)(20)(39)(40)(41)(42)(43)(44)(45), four used quasi-experimental trials (46)(47)(48)(49) and four used RCT (50-53) (Table I).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…1); five case studies (17,(22)(23)(24)(25)(26) were excluded and nine studies (24,(27)(28)(29)(30)(31)(32)(33)(34) were removed due to difficulties in extracting the outcome measurements. Four systematic reviews (35)(36)(37)(38) were also excluded. An assessment of the remaining 18 studies revealed that 10 used a single-arm prospective design (18)(19)(20)(39)(40)(41)(42)(43)(44)(45), four used quasi-experimental trials (46)(47)(48)(49) and four used RCT (50-53) (Table I).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…MSCs may be useful for this purpose as they are readily present within the bone marrow of adults in addition to being a precursor cell type to the chondrocytic lineage. 18,25 Further, bone marrow MSCs have been shown to maintain stemness and chondrogenic differentiation capacity upon expansion in vitro allowing sufficient cell numbers for use in tissue engineering practices. 23,26 However, previous studies have shown that while MSCs do undergo chondrogenesis, less matrix is produced by MSCs than by chondrocytes cultured similarly.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Other studies have shown that BMSC has a stronger ability of chondrogenic differentiation than ADSC. Filardo et al [26] reviewed 90 research papers on the clinical application of ADSC chondrogenic differentiation, including 72 preclinical studies and 18 clinical experiments. Only 2 clinical experiments recommended ADSC.…”
Section: Application Of Chondrogenic Differentiationmentioning
confidence: 99%